The sufficiency of contrastive interpretation in the novel "As If It Were a Canopy" by Moroccan Author Suad Al-Nasser, as a model - Harboul, Sanae (Journal of Arabic Language Sciences and Literature, 2025)
This study aims to explore the topic of "Contrastive Interpretation in Contemporary Morocca Women’s Novels," by adopting the approach of Dr. Mohamed Bazzi, which seeks to open up to mechanisms that contribute to the study of narrative discourse by linking it to life and values through a comprehensive approach based on modern rhetorical techniques, foremost among them contrast. This enables the reader, through numerous dualities, to delve into the narrative, probe the depths of the discourse, and connect it to human reality according to a new perspective. The study was applied to the novel "As If It Were a Shadow" by the Moroccan writer Suad Al-Nasser, in which the study attempted to trace the various contrasts present in the novel at the level of the title, spaces, events, and values, and to understand their significance and function.